Existence and Asymptotic Stability of Solutions of a Functional Integral Equation via a Consequence of Sadovskii's Theorem. (15th July 2014) - Chlebowicz, Agnieszka; Darwish, Mohamed Abdalla; Sadarangani, Kishin
Abstract : Using the technique of measures of noncompactness and, in particular, a consequence of Sadovskii's fixed point theorem, we prove a theorem about the existence and asymptotic stability of solutions of a functional integral equation. Moreover, in order to illustrate our results, we include one example and compare our results with those obtained in other papers appearing in the literature.